TIMP3::ALK fusions characterize a distinctive myxoid fibroblastic tumor of the vocal cords: a report of 7 cases - Klubickova, Natalie; Michal, Michael; Agaimy, Abbas; Zidar, Nina; Pavlovsky, Michal; Yorita, Kenji; Grossmann, Petr; Hajkova, Veronika; Ptakova, Nikola; Steiner, Petr; Michal, Michal (Virchows Archiv, 2022)
We report 7 cases of an indolent, variably myxoid tumor of the vocal cords, characterized by overt cellular atypia with large cells containing intranuclear and intracytoplasmic vacuoles, delicate curvilinear vessels, and sparse inflammatory infiltrate. Six patients were male, aged 15 to 65 years, and 1 patient was a 54-year-old female. All tumors were located in the superficial portion of the vocal cord. One patient suffered a recurrence that was completely resected; all patients with available follow-up data currently have no evidence of disease. The tumors contained alternating areas with myxoid stroma and more compacted regions with tumor cells organized in short fascicles, interwoven with delicate curvilinear vasculature. Overt cellular atypia with large cells containing intranuclear and intracytoplasmic vacuoles or resembling ganglion cells was present in all cases but mitoses and necrosis were absent. ALK immunostaining was positive in all cases, while most tumors were negative for smooth muscle actin. Targeted RNA-sequencing revealed an identical TIMP3::ALK fusion with exon 1 of TIMP3 gene being fused with exon 12 of ALK gene in all analyzable cases. For various reasons discussed, it remains unclear whether this tumor represents a mere subtype of IMT or a separate entity. Nevertheless, it is a morphologically distinct and diagnostically challenging lesion that needs to be recognized by surgical pathologists in order to prevent overdiagnosis in this clinically very delicate area.
CRIS-Team WoS Importer:2022-08-26